Femtosecond Laser–Assisted Lamellar Keratectomy for Corneal Opacities Secondary to Anterior Corneal Dystrophies: An Interventional Case Series. Issue 1 (January 2016) - Steger, Bernhard; Romano, Vito; Biddolph, Simon; Willoughby, Colin E.; Batterbury, Mark; Kaye, Stephen B.
Abstract : Purpose: To report results of femtosecond laser–assisted lamellar keratectomy (FLK) for corneal opacities secondary to anterior corneal dystrophies. Methods: Patients with a clinical diagnosis of Reis–Bücklers corneal dystrophy, granular corneal dystrophy, lattice corneal dystrophy, and macular corneal dystrophy were treated. FLK was performed to remove a central corneal free cap of 9.5 mm in diameter at a depth of 110 to 140 μm on which histological analysis was undertaken. Preoperative and postoperative refraction, best spectacle-corrected visual acuity, corneal topography results, and color photographs were recorded. Postoperative in vivo confocal microscopy of the cornea was performed. Changes in uncorrected visual acuity and best spectacle-corrected visual acuity, keratometry, refractive error, corneal irregularity, residual or recurrent central corneal opacities, and corneal haze were used to assess the outcome. Results: Eight eyes of 6 patients were treated. The clinical diagnosis was confirmed histologically in all cases. Visual acuity improved significantly from 0.49 ± 0.2 logMAR to 0.14 ± 0.13 logMAR after a mean follow-up of 29 ± 14 (range 8–54) months. Residual central stromal opacities were noted in 5 of 8 eyes immediately postoperatively. Clinically significant recurrence of disease was noted in 1 eye. Keratometry and refraction remained stable, and no further surgical intervention was needed. Patients with stromal corneal dystrophies had worse outcome than those with Reis–Bücklers corneal dystrophy. Conclusions: In this case series, FLK provided both therapeutic and diagnostic intervention, delaying more invasive surgery. In vivo confocal microscopy showed signs of postoperative corneal stromal neuropathy.